PENGARUH MANAJEMEN SEKOLAH DAN MOTIVASI KERJA TERHADAP KINERJA GURU SEKOLAH MENENGAH ATAS (SMA) ADVENT KOTA SUKABUMI - Wyler Pakpahan (JURNAL BUANA INFORMATIKA CBI, 2016)
Education is the most important factor that really help human resource development in any country, as it is shown that the modern countries already had absorbed a good quality of education. Adventist Senior High School Sukabumi is one of the private Senior High School that give share and contribution in helping the nation in the develop a better education, but in the reality, it has not got the optimal purpose yet and it needs more attention from the stakeholders and any others who concern to the school in operating the daily activities both in School Management ang Motivation to Teacher’s Performance in Teaching. The purpose of the research is to analyze the influence of School Management and Motivation of Teacher’s Performance in Teaching. The research is applied by using sampling method with the total sample 31 teachers who are direct involved, and the data collecting was done by interviewed and answered question of the questioner paper. The real data was analyzed in quantitative. The result is applied at Senior High School at Adventist Senior High School Sukabumi, by using sampling analyzing the Correlation Pearson Product Moment and School Management with Motivation of Teacher’s Performance of Teaching was 0,526 at the low scale. School management with Teacher Performance of Teaching is 0,140 at the middle scale. The Teacher’s Motivation and the Teacher’s Performance of Teaching is 0,972 at the high scale. Keyword : School Management, Working Motivation and Teacher’s Performance